Discontinued Mediations: Preludes to Fractured Thinking. Issue 3 (September 2021) - McCaffery, Steve
Abstract : This text is offered as an alternative to the normative academic paper. It seeks to establish incompletion as a quantum phenomenon. It arranges thinking into aphoristic moments. Its subject-scope embraces ontology, language, artistic innovation, and subjectivity.